An indeterminate nodule in the cirrhotic liver discovered by surveillance imaging is a prelude to malignancy. Issue 8 (25th August 2014) - Beal, Eliza W.; Albert, Scott; McNally, Megan; Shirley, Lawrence A.; Hanje, James; Michaels, Anthony J.; Black, Sylvester M.; Bloomston, Mark; Schmidt, Carl R.
<x xml:space="preserve">Abstract</x> Background Surveillance imaging often shows indeterminate lesions in the cirrhotic liver, which may represent early hepatocellular carcinoma (HCC), dysplastic or regenerative nodules, or vascular shunts. The risk of HCC after identification of an indeterminate nodule is not well described. Methods We identified 252 patients with cirrhosis and at least one indeterminate nodule discovered on surveillance imaging over a 4‐year period. The incidence of HCC development within 2 years of nodule identification was measured along with baseline risk factors associated with developing HCC. Results The incidence of HCC in this population was 21% (53 of 252), and risk factors associated with HCC included chronic viral hepatitis, male gender, and low platelet count. The median time from identification of an indeterminate nodule to diagnosis of HCC was 2.7 months. Patients with indeterminate nodules who developed HCC were more likely have to have an indeterminate nodule with arterial enhancement. Conclusions The 2‐year incidence of HCC in the setting of cirrhosis and an indeterminate nodule discovered by surveillance imaging may be as high as one in five persons. Early follow‐up imaging, biopsy, or empiric treatment should be considered for those at higher risk. Further, this population is well suited for early detection biomarker and chemoprevention studies. J. Surg. Oncol. 2014; 110:967–969. © 2014 Wiley Periodicals, Inc.